A STUDY OF THE BRITISH FORWARD POLICY AFTER THE ANNEXATION OF PUNJAB - Riaz Hussain Mastoi,; Saad Ahmed Khan, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
With the beginning of the great game, the British government felt a threat from the north-west border and decided to cross the Indus in 1839 and reached Kabul. With the death of Ranjeet Singh colonial government also occupied Sindh in 1843. In Punjab the Sikh government lasting its breath. The British government decided to take over Punjab. So the British won the First Sikh War and similarly won the Second Sikh War and annexed Punjab to the British Government. In Dera Ghazi Khan, the British government faced stiff resistance from the Baloch tribes. English army used artillery in war with the tribes. The British government tried to control the Baloch tribes by force but failed and the advance towards Balochistan slowed down. In these circumstances, the government took care of administrative matters through various policies. The advance towards Balochistan was stopped and the closed border policy was implemented, but later Sandeman negotiated with the tribes and subdued them first under the reconciliation policy and then under the principle of divide and rule by introducing the Tamandari system and subordinating them to the Tamandars. Implemented to make the forward policy successful. Sandeman's policy was successful and British rule extended to Balochistan. The English government confined the people in grip through Tamandars, as well as administratively Deputy Commissioners, Revenue Officers, Collectors, and Patwaris. And his strategy to go beyond the Punjab-Baluchistan border was successful. Sandeman proved that the state could be extended not only by force but also by diplomatic policy and his conciliatory policy was well received. As per Sandeman Policy the tribes of Dera Ghazi Khan were engaged by the British policy and now they were in a position to occupy Balochistan and Kalat. It was very important for the British to establish their grip in this area so that may become easy and decrease the pressure on the western border from Iran, Afghanistan and Russia. This research article explains and highlights the strategies and policies adopted regarding expanding British rule from Punjab to Balochistan.